(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstrack : In Government Regulation Number 101 Year 2000 on Education and Training of Civil Servants Position stated that the training is the process of organizing learning in order to improve the ability of the Civil Service / Administrative Civil State. The third term (education, training, development) are related to each other and sometimes complementary. This research was conducted at the Regional Employment Board Tomohon, in particular education and training. Implementation of Education and Training (Training) in the State Civil Apparatus Tomohon City Government is one of the government’s efforts to improve the quality of ASN in terms of national awareness, personality and ethics of the State Civil Apparatus. This research was conducted in order to determine how the performance of Regional Employment Agency in organizing the State Civil Training Apparatus in Tomohon City Government. The research was conducted using qualitative methods, with 10 informants. The study was conducted with technical documentation study, observation and interviews and data analysis Miles and Haberman model analysis, namely data reduction, data presentation and conclusion. The results showed: Performance of Tomohon City Regional Employment Board in organizing the ASN Training has been good enough because it is supported by the implementation of a training program that is running well; the quality of human resources personnel a good employee and organizational support. Factors inhibiting the performance of BKD organizing ASN Training in Tomohon is a factor supporting infrastructures are not yet supporting and budget and employee discipline. While supporting factor is the support organization, partnerships, human resource personnel with adequate and continuous training. The effort that has been done is to include in the future work program constraints and needs required by BKD forward in the vision, mission, goals and objectives of the organization, in the form of provision of training facilities and infrastructure such as buildings and dormitories training; improving the quality and capacity of the resource; improve discipline and performance of civil servants; improve the well-being and improve the coordination / consultation of personnel affairs. Keywords: Education; training; BKD performance.